Reconstruction of Mascot Dance Gending Sekar Tunjung | Rekontruksi Gending Tari Maskot Sekar Tunjung - Andika, I putu Restu; Hartini, Ni Putu (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Blahkiuh Traditional Village is the capital city of Abiansemal District, Badung Regency, Bali Province which has famous artistic assets in Bali such as the Kecak Dance, Parwa, Arja Basur, Joged Bumbung, and carving art. The mascot dance that has sunk long ago with the aim of being rebuilt. Various attempts have been made by the author, such as exploring holding hearings with several related officials and several existing art activists, in order to obtain information and activities8that can be superior. After obtaining the information, the author tries to assist in this reconstruction process so that this reconstruction process can run smoothly and quickly. Blahkiuh village has very good potential, especially in performing arts and has a performing art that is used as a village icon in the form of the Sekar Tunjung mascot dance. Sekar Tunjung consists of 2 syllables, namely sekar and tunjung, sekar which means flower, and tunjung which means purity. In Bali, the lotus is believed to emerge from the navel of Lord Vishnu, with Brahma sitting in the center of the flower. Some believe that the Lord's hands and feet are like lotuses and his eyes are shaped like lotus petals, his gaze and touch are said to be as 6gentle as lotus buds. 9Hinduism also teaches that in every person there is a lotus spirit. 7The lotus plant is one of the plants used to describe human life. The meaning of this lotus plant is much related to personal strength,9 a reminder that human life is only temporary and also about human life that should be regardless of the environment. Based on the statement above, the author chose Blahkiuh village as a partner in implementing the MBKM Thematic Work Lecture program. With the aim of helping in the Mascot Dance reconstruction program and accommodates the potential to develop it and has 1an important role in all activities of the Blahkiuh village community.